Thrombus and antiplatelet therapy in type 2 diabetes mellitus - Viswanathan, Girish N.; Marshall, Sally M.; Schechter, Clyde B.; Balasubramaniam, Karthik; Badimon, José J.; Zaman, Azfar G. (Thrombosis and Haemostasis, 2012)
Type 2 diabetes mellitus (T2DM) is associated with higher rates of thrombotic complications in patients with coronary artery disease (CAD) despite optimal medical therapy. Thrombus area was measured in T2DM and non-diabetic patients receiving aspirin and clopidogrel 7–10 days after troponin positive Non ST-elevation acute coronary syndrome (NSTE-ACS). Secondly, we assessed response to clopidogrel in naive patients with T2DM and stable CAD in a randomised controlled trial. Thrombus area was measured by Badimon chamber and platelet reactivity by VerifyNow®. In T2DM patients presenting with NSTE-ACS, thrombus area was greater compared to non-diabetic patients (mean ± SD, 20,512 ± 12,567 [n=40] vs. 14,769 ± 8,531 [n=40] μm2/mm, p=0.02) Clopidogrel decreased thrombus area among stable CAD patients with T2DM (mean ± SD, Clopidogrel [n=45]: 13,978 ± 5,502 to 11,192 ± 3,764 μm2/mm vs. placebo [n=45]: 13,959 ± 7,038 to 14,201 ± 6,780 μm2/mm, p<0.001, delta values: clopidogrel vs. placebo, mean ± SD, 2,786 ± 4,561 vs. –249 ± 2,478, p<0.0005). Only 44% of patients with CAD and T2DM responded to clopidogrel as per VerifyNow® (cut-off PRUz value of ≥240). Importantly, no correlation was observed between thrombus area and VerifyNow® values (rho 0.08, p=0.49). Thrombus area values were similar among hypo-responders and good responders to clopidogrel (mean thrombus area ± SD: 12,186 ± 4,294 vs. 10,438 ± 3,401; p=0.17). Type 2 diabetes mellitus is associated with an increased blood thrombogenicity among NSTE-ACS patients on currently recommended medical therapy. Thrombus area was significantly reduced in all stable CAD patients independently of their response to clopidogrel therapy.
Keywords: Type 2 diabetes mellitus; acute coronary syndrome; stable coronary artery disease; thrombus; antiplatelet therapy